2017
DOI: 10.1128/jb.00127-17
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-Specific Enzyme IIA of the Phosphoenolpyruvate:Carbohydrate Phosphotransferase System Modulates Chitin Signaling Pathways in Vibrio cholerae

Abstract: In Vibrio cholerae, the genes required for chitin utilization and natural competence are governed by the chitin-responsive two-component system (TCS) sensor kinase ChiS. In the classical TCS paradigm, a sensor kinase specifically phosphorylates a cognate response regulator to activate gene expression. However, our previous genetic study suggested that ChiS stimulates the non-TCS transcriptional regulator TfoS by using mechanisms distinct from classical phosphorylation reactions (S. Yamamoto, J. Mitobe, T. Ishi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 92 publications
7
16
1
Order By: Relevance
“…5a). ChiS activity is also negatively regulated by carbon catabolite repression (CCR) (23), suggesting that the chitin utilization program is suppressed in the presence of preferred carbon sources. The mechanism underlying CCR-dependent inhibition of ChiS, however, remains unclear and will be the focus of future work.…”
Section: Discussionmentioning
confidence: 99%
“…5a). ChiS activity is also negatively regulated by carbon catabolite repression (CCR) (23), suggesting that the chitin utilization program is suppressed in the presence of preferred carbon sources. The mechanism underlying CCR-dependent inhibition of ChiS, however, remains unclear and will be the focus of future work.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate regulation of the chitin utilization program in V. cholerae, most studies employ the chitobiose utilization operon (chb) (10,11,17,18). The chb operon encodes the genes required for uptake and catabolism of the chitin disaccharide chitobiose and is highly induced in the presence of chitin oligosaccharides (7).…”
mentioning
confidence: 99%
“…Though a link between chitin utilization and quorum sensing has previously been suggested, it has not been directly studied (16). To investigate regulation of the chitin utilization program in V. cholerae, most studies employ the chitobiose utilization operon (chb) (10,11,17,18). The chb operon encodes the genes required for uptake and catabolism of the chitin disaccharide chitobiose, and is highly induced in the presence of chitin oligosaccharides (7).…”
mentioning
confidence: 99%
“…ChiS is the master regulator of the chitin utilization program in V. cholerae, and we have recently shown this protein is a direct transcriptional activator required for induction of the chb locus (9,10). Previous work has shown that carbon catabolite repression (CCR) can also play a role in regulating chitin responsive phenotypes including ChiS-dependent induction of chb and natural transformation (18,19). In addition, our group has previously found that the cell division licensing factor SlmA plays an essential role in activating chb expression (11).…”
mentioning
confidence: 99%